The Implementation of P5 Local Wisdom Themes in the Independent Curriculum in Elementary Schools - Denaya Mehra Syaharani; Achmad Fathoni (Universitas Pendidikan Ganesha, 2023)
The pancasila student profile strengthening project was created to optimize students' abilities by strengthening the pancasila student profile, which was develop based on a theme. However it is not introduced directly in every educational institution, but rather gradually and is not limited to the content basis. This research aims to analyse students' enthusiasm for implementing P5 in the implementation of the new curriculum by focusing on the theme of local wisdom that develops through project-based learning. The qualitative description method was applied in this study. This study is based on primary and secondary data. This study's principal data sources are fourth-grade teachers and fourth-grade learners, while the secondary data are the results of observation and documentation in the form of project modules and the results of P5 implementation activities on the theme of local wisdom. Data analysis technique used is interactive, and it consists of four components of the analysis process: data collection, data reduction, data presentation, and drawing conclusions. The study's findings revealed that learners were highly enthusiastic about the application of P5. Although it was relatively new in the implementation of the independent curriculum, it was able to become a new value for students and teachers so that the projects carried out did not hinder the learning process by determining the choice of themes by the teacher. in accordance with the facilities and capabilities of the school. Improving the character values of students according to the profile of Pancasila students.